Antecedents and implications of disruptive innovation: Evidence from China - Wan, Feng; Williamson, Peter J.; Yin, Eden (Technovation, 2015)
A growing recognition of the importance of disruptive innovation has led researchers to examine the question of how disruptive innovation comes about and to what extent it reflects “discovery” versus “creation” of opportunities. Earlier research has focused on the organisational preconditions for disruptive innovation to arise. Much less attention has been paid to the role of innovation processes, including their goals and design, in promoting disruptive innovation. In this paper we aim to begin to fill this gap by better understanding how new innovation processes can act as antecedents for disruptive innovation. We adopt an inductive theory-building methodology using a set of case studies of Chinese firms to develop propositions about how novel R&D and production processes can foster disruptive innovation. We find that in the case of China the adoption of new innovation processes that re-define the focus of innovation and re-engineer traditional R&D processes in ways that allow the novel deployment of Chinese cost advantages can create offerings that incorporate the key elements of disruptive innovation in the sense that they challenge incumbents׳ established business models. Realising disruptive innovation opportunities requires proactive initiatives. We conclude by discussing the managerial implications and possible responses as well as directions for future research. •We explore how new innovation processes act as antecedents for disruptive innovation.•We use inductive theory-building based on a set of case studies of Chinese firms.•China is a significant source of disruptive innovation.•Novel R&D and production processes can foster disruptive innovation.•Realising disruptive innovation opportunities requires proactive initiatives.